THE EFFECT OF CONSUMING RED GUAVA ON INCREASING HEMOGLOBIN LEVELS IN PREGNANT WOMEN - Rehmaita Malem; Muhibbullah Ali Puteh; Mursyidah Mursyidah (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
One of the global targets is the effort to reduce maternal mortality rates. In 2020, there were 4,627 maternal deaths recorded, caused by bleeding (28.29%), hypertension (23%), and circulatory system disorders (4.94%). The primary cause of maternal death is bleeding. This study aims to determine the effect of consuming red guava seeds on the increase in hemoglobin levels in pregnant women. The research method used is a quasi-experimental design with a one-group pretest-posttest design. The study was conducted at the KIA Clinic of UPTD Seunuddon Health Center in North Aceh Regency from June 3, 2024, to June 14, 2024, with a sample size of 47, using non-probability sampling, specifically accidental sampling. The results obtained from the paired sample test before and after consuming red guava seeds showed a sig (2-tailed) value of 0.000 < 0.05, indicating that there is an effect of consuming red guava seeds on increasing hemoglobin levels in pregnant women at the KIA Clinic of UPTD Seunuddon Health Center, North Aceh Regency. The researcher concludes that consuming red guava seeds can increase hemoglobin levels in pregnant women.